Le multilatéralisme onusien à l’épreuve de la gouvernance climatique - Mélanie Dubuy (VertigO, 2018)
After the failure of Copenhagen in 2009, doctrine has talked about a multilateralism in crisis. This multilateralism characterized by state equality, reciprocity and continuity has appeared utterly incapable of bringing good cooperation between States so as to reach the adoption of a binding agreement to organize the fight against climate warming. This multilateralism is usually opposed to alliances occasionally formed and characterised by a geopolitical logic of power, of selectivity. The Copenhagen failure has brought forward this tough geopolitical logic (hard gaps were created between developed and developing States, emerging economies) revealing a very weak climate governance that was striving to cope with an already very complex and multiscale issue. As numerous political scientists have proposed other suggestions, many States have preferred the very limited structure of clubs. The COP 21 and the Paris agreement have put back on track the UN process that was gridlocked even if the oppositions of viewpoints have not vanished and the coalitions of interests are remaining. The solution of multilateralism that enables a balance and flexible solution between unilateralism and the partly binding character of the agreement explains this success as well as the increase involvement of civil society.